Involvement of the Spinal Serotonergic System in the Analgesic Effect of [6]-Shogaol in Oxaliplatin-Induced Neuropathic Pain in Mice - Juan Gang; Keun-Tae Park; Suyong Kim; Woojin Kim (Pharmaceuticals, 2023)
Oxaliplatin is a chemotherapy drug that can induce severe acute neuropathy in patients within hours of treatment. In our previous study, 10 mg/kg [6]-shogaol (i.p.) significantly alleviated cold and mechanical allodynia induced by a 6 mg/kg oxaliplatin injection (i.p.); however, the precise serotonin-modulatory effect has not been investigated. In this study, we showed that intrathecal injections of NAN-190 (5-HT1A receptor antagonist, 1 µg) and MDL-72222 (5-HT3 receptor antagonist, 15 µg), but not ketanserin (5-HT2A receptor antagonist, 1 µg), significantly blocked the analgesic effect of [6]-shogaol (10 mg/kg, i.p.). Furthermore, the gene expression of the serotonin-synthesizing enzyme tryptophan hydroxylase 2 (TPH2) and serotonin levels in the spinal cord and serum were significantly downregulated (p < 0.0001 and p = 0.0002) and upregulated (p = 0.0298 and p = 0.0099) after oxaliplatin and [6]-shogaol administration, respectively. Moreover, both the gene and protein expression of the spinal serotonin receptors 5-HT1A and 5-HT3 significantly increased after [6]-shogaol injections (p < 0.0001). Finally, intrathecal injections of both receptor agonists (8-OH-DPAT; 5-HT1A receptor agonist, 10 µg and m-CPBG; 5-HT3 receptor agonist, 15 µg) mimicked the effects of [6]-shogaol in oxaliplatin-injected mice. Taken together, these results demonstrate that [6]-shogaol attenuates oxaliplatin-induced neuropathic pain by modulating the spinal serotoninergic system.